Prevelance Survey for Assessing Intensity of Group A Beta Hemolytic Streptococci (GABHS) Subclinical Infection Rate in School Children: A Cross Sectional Study (Global Journal of Medical Research, 2013)
Background: GABHS infections and their sequelae Rheumatic fever and rheumatic heart disease have a worldwide distribution and pose an important health problem. In developing countries it remains as an endemic disease. Objectives: The study is aimed to estimate prevalence and factors associated with the same among school children aged 6–12years. Materials and Methods: This cross-sectional survey was carried out from February to July 2010, in the diagnostic laboratory of Microbiology department. The study group was divided into four groups, namely, Group A; Group B; Group C; and Group D. A total of 1769 eligible children were enrolled for sampling of these schools. For each enrolled child in the study, a standard culture and antibiogram test with the Lancefield grouping technique was done in the assessment of the outcome. Results: Among 1769 participants, 1029 (58.2%) were boys and 740 (41.8%) were girls. The overall prevalence of GABHS was estimated 27.9%. Group A 35.62%, Group B 37.5%, Group C 34.8%, and Group D 23.7%. Higher prevalence was found in 6-10 years aged; the prevalence percentage declined with increase in age and showed lowest prevalence in subjects above 10 years of age. The prevalence was higher in boys as compared with girls. The sensitivity was highest for vancomycin 100% and the resistance was highest for amoxicillin 79.1%. Conclusions: The study confirmed that the prevalence of GABHS is 27.9%. Overall prevalence shows an endemic situation. Therefore, it is recommended that local health sectors should make provision for regular screening and prophylaxis.
Keywords: antibiogram; factors associated; GABHS; prevalence; school children